Pollen grains and pollinia in four Southamerican palustrine species of Habenaria (Orchidaceae) - Passarelli, Lilian Mónica (2010)
The massulae and pollen grains in pollinia of four palustrine South American species of Habenaria, H. bractescens, H. gourlieana, H. paucifolia and H. secunda were studied here for the first time using light, scanning, and transmission electronic microscopy. The pollinia have acalymmate, piriform or tabular massulae. Filiform elastoviscin threads are formed between the pollen grains of pollinia, allowing them to stick together. The pollen grains are inaperturate, grouped into calymmate tetrads, and have reticulate or reticulum-like, heterobrochate exine. Reticulate ornamentation consists of irregular, rounded, wide or narrow, continuous muri, while reticulum-like ornamentation is formed by discontinuous, partial muri, superficially smooth or with spherical micro-granules, intermingling with some isolated elements that can be interpreted as pila. The wall structure of individual pollen grains differs according to their position in the tetrads: outside walls develop complete exine and intine, with columellae, while the walls inside the pollinium lack exine or develop only a much reduced one. Palynological characters differentiate the species: pyriform massulae, triangular in outline, occur in H. gourlieana, H. paucifolia and H. secunda, while tabular massulae, oblong in outline, characterise H. bractescens. Ornamentation also distinguishes H. gourlieana grains, with interrupted, discontinuous muri, from the other three species, bearing reticulate grains. Elastoviscin filiform threads, which were found to be lipidic in nature, are simple or ramified, and some bear pores (in H. bractescens). Branched filiform threads characterise H. bractescens and H. secunda, while unbranched, filiform threads correspond to H. gourlieana and H. paucifolia.